Design and fabrication of reliability test device for telephone cord pulling strength and slip down test - Syahidah Nafisa, Abdul Malik (2009)
This project is to design and fabricate reliability test device for telephone cord pulling strength and slip down test. The main problem is the reliability test of curl-cord pulling strength and slip down test at Panasonic Company does not have test device specifically. When measures the length of the curl cord at 45°, the curl cord was bending and makes the result not precise. It also happen for slip down test where it difficult to define the exactly view or moment when the base unit start moving. It is important to further improve the current design of reliability test device for curl cord pull strength test and also slip down test to make the result from the test is more precise and accurate. The first stage is design or sketch a few concepts the reliability test device. Second stage is made a conceptual process which is selecting the best design as a final design before further to fabrication process. For this stage, to choose the best concept the concept selection were done. And the last stage is fabricating the device by using the final design that has been chosen. A few processes involved to fabricate the device which are measuring and marking, cutting, joining, drilling, finishing, assembling and lastly is spraying process.